2003
DOI: 10.1128/iai.71.8.4506-4515.2003
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Specific T-Cell Responses, Opsonizing Antibodies, and Protection againstPlasmodium chabaudi adamiInfection in Mice Vaccinated with Genomic Expression Libraries Expressed in Targeted and Secretory DNA Vectors

Abstract: It has been proposed that a multivalent malaria vaccine is necessary to mimic the naturally acquired resistance to this disease observed in humans. A major experimental challenge is to identify the optimal components to be used in such a multivalent vaccine. Expression library immunization (ELI) is a method for screening genomes of a pathogen to identify novel combinations of vaccine sequences. Here we describe immune responses associated with, and the protective efficacy of, genomic Plasmodium chabaudi adami … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…with BC construct 1. Opsonization of IRBC and subsequent internalization and destruction by macrophages have been shown to be a major factor contributing to a reduction in parasitemia during crisis in P. chabaudi mouse models (24)(25)(26). The opsonizing capacity of prechallenge sera taken from mice vaccinated i.m.…”
Section: Expression Of Protein Encoded By Bicistronic Plasmids In Vitromentioning
confidence: 99%
“…with BC construct 1. Opsonization of IRBC and subsequent internalization and destruction by macrophages have been shown to be a major factor contributing to a reduction in parasitemia during crisis in P. chabaudi mouse models (24)(25)(26). The opsonizing capacity of prechallenge sera taken from mice vaccinated i.m.…”
Section: Expression Of Protein Encoded By Bicistronic Plasmids In Vitromentioning
confidence: 99%
“…In the present study, we have used expression library immunization (ELI) as an approach to identify new combinations of crossprotective antigens within the malaria genome, using P. c. adami in mice as a model test system. ELI has been shown to be protective against Mycoplasma (2), Leishmania (43), and Plasmodium, where we showed that mice were significantly protected against virulent P. c. adami DS infection by vaccination with a homologous genomic expression library (46,58). We hypothesized that our library contains multiple antigen sequences, many of which could be novel hypothetical sequences known to exist in the genome (18), and that this multivalent antigen cocktail may elicit good cross-protection due to sequence conservation between strains.…”
mentioning
confidence: 71%
“…A genomic library from P. chabaudi adami DS was produced in the DNA vaccine vector VR1020 as described previously (46,58). A total of 10 pools (termed 3KA-3KJ), each comprising approximately 3,000 individual clones, were constructed and stored at Ϫ80°C as glycerol stocks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations